The Effect of Academic Supervision and Managerial Ability on Teacher Competence Through Work Motivation - Yuniyanto, Anang; Fakhruddin, Fakhruddin; Mahmud, Amir (Educational Management, 2024)
The objective of this study is to examine the causal relationships between academic supervision and the managerial abilities of principals, and their impact on teacher competence. This analysis will also consider job motivation as a mediating component in this relationship. The present study employs a quantitative methodology. The study's sample included 125 teachers from seven private vocational schools located in Temanggung Regency. The employed sample methodology was random sampling. The research instrument employed in this study consisted of a questionnaire that underwent initial testing to establish its validity and reliability. In the context of hypothesis testing, the process of data analysis often involves employing path analysis and the Sobel test to examine the role of mediating variables. The study's findings indicate that there exists a significant relationship between academic supervision, administrative ability of school principals, and work motivation. The influence of academic supervision and managerial abilities of principals on teacher competence is evident. The mediating role of work motivation is observed in the relationship between academic supervision, principal's administrative abilities, and teacher competence.